Arbuscular mycorrhizal fungi occurrence in revegetated areas after bauxite mining at Porto Trombetas, Pará State, Brazil - Caproni, Ana Lucy; Franco, Avílio Antônio; Berbara, Ricardo Luis Louro; Trufem, Sandra Botelho; Granha, José Rodolfo Dantas de Oliveira; Monteiro, Ana Beatriz (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this study was to evaluate the structure and diversity of arbuscular mycorrhizal fungi (AMF) in revegetated areas at Porto Trombetas, Pará, Brazil. Composite samples were collected in August (dry season) and April (wet season) in areas with top soil after 2, 4, 6, 12 and 16 years of revegetation, in area without the top soil or vegetation, and in a pristine forest. The AMF spores were extracted, and the species identified. The relative density and frequency of occurrence of each species, the Shannon-Wiener and Simpson indexes were calculated. The results indicated that the density of AMF spores did not differ significantly with season. However, the number of AMF species was significantly higher in the dry season at the pristine forest and in the area two years after revegetation. Among the AMF species, Glomus macrocarpum and Acaulospora mellea were represented in higher numbers. After two years of planting, the diversity was highest and the dominance of AMF species was lowest. The addition of top soil with the planting of mycorrhizal seedlings were efficient to colonize areas with AMF after open cast bauxite mining.